Assessing the impact of liver fat fraction on portal hemodynamics in nonalcoholic fatty liver disease using MRI proton density fat fraction and MRI 4D Flow - Wang, Li-Zhen; Li, Wen-Qiang; Li, Yao; Li, Xiao-Yan; Ju, Shuai (Frontiers in Medicine, 2025)
BackgroundNonalcoholic fatty liver disease (NAFLD) is a prevalent condition with significant implications for liver and cardiovascular health. Alterations in portal hemodynamics due to hepatic steatosis remain poorly understood.AimThis study aims to explore the correlation between liver fat fraction (FF) and portal hemodynamics in NAFLD patients.MethodsA retrospective observational study was conducted involving 125 clinical suspected NAFLD patients. Liver FF was measured using MRI proton density fat fraction (PDFF). MRI 4D Flow was used to assess portal hemodynamic parameters, including flow velocity, flow volume, and portal area. Statistical analyses examined the relationships between liver FF and hemodynamic parameters.ResultsLiver FF was negatively associated with portal peak flow velocity (r = −0.33) and portal mean flow velocity (r = −0.49), but was positively correlated with portal area (r = 0.39). No correlation was found in liver FF and portal flow volume (p = 0.114). Portal peak velocity demonstrated AUCs of 0.69 (95% CI: 0.57–0.82) for differentiating G0 from G1-3, 0.70 (95% CI: 0.60–0.79) for G0-1 versus G2-3, and 0.57 (95% CI: 0.44–0.69) for G0-2 versus G3. Portal mean velocity demonstrated AUCs of 0.84 (95% CI: 0.76–0.92) for differentiating G0 from G1-3, 0.78 (95% CI: 0.69–0.86) for G0-1 versus G2-3, and 0.70 (95% CI: 0.60–0.79) for G0-2 versus G3. Portal area demonstrated AUCs of 0.79 (95% CI: 0.70–0.78) for G0 versus G1-3, 0.78 (95% CI: 0.48–0.92) for G0-1 versus G2-3, and 0.84 (95% CI: 0.76–0.92) for G0-2 versus G3.ConclusionLiver FF is a significant determinant of portal hemodynamics in NAFLD patients. These findings underscore the potential of integrating liver FF and portal hemodynamic assessments into clinical practice for detection and management of NAFLD progression.